Linking distress of financial institutions to macrofinancial shocks - Alexander Al-Haschimi; Stéphane Dées; Filippo di Mauro; Martina Jančoková (European Central Bank (ECB), 2014)
This paper links granular data of financial institutions to global macroeconomic variables using an infinite-dimensional vector autoregressive (IVAR) model framework. The approach taken allows for an assessment of the two-way links between the financial system and the macroeconomy, while accounting for heterogeneity among financial institutions and the role of international linkages in the transmission of shocks. The model is estimated using macroeconomic data for 21 countries and default probability estimates for 35 euro area financial institutions. This framework is used to assess the impact of foreign macroeconomic shocks on default risks of euro area financial firms. In addition, spillover effects of firm-specific shocks are investigated. The model captures the important role of international linkages, showing that economic shocks in the US can generate a rise in the default probabilities of euro area firms that are of a significant magnitude compared to recent historical episodes such as the financial crisis. Moreover, the potential heterogeneity across financial firms' response to shocks, which motivates an approach based on granular information, is investigated. By linking a firm-level framework to a global model, the IVAR approach provides promising avenues for developing tools that can explicitly model spillover effects among a potentially large group of firms, while accounting for the two-way linkages between the financial sector and the macroeconomy, which were among the key transmission channels during the recent financial crisis.
Keywords: C33; G33; 330; corporate sector credit risk; default frequencies; GVAR; infinite-dimensional VAR